Microbial Biofilms in Healthcare: Formation, Prevention and Treatment - Vickery, Karen (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Biofilms are ubiquitous and their presence in industry can lead to production losses. However, nowhere do biofilms impact human health and welfare as much as those that are found contaminating the healthcare environment, surgical instruments, equipment, and medical implantable devices. Approximately 70% of healthcare-associated infections are due to biofilm formation, resulting in increased patient morbidity and mortality. Biofilms formed on medical implants are recalcitrant to antibiotic treatment, which leaves implant removal as the principal treatment option. In this book, we investigate the role of biofilms in breast and dental implant disease and cancer. We include in vitro models for investigating treatment of chronic wounds and disinfectant action against Candida sp. Also included are papers on the most recent strategies for treating biofilm infection ranging from antibiotics incorporated into bone void fillers to antimicrobial peptides and quorum sensing.